2017
DOI: 10.3389/fimmu.2017.00110
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-Producing CD1dhiCD5+ Regulatory B Cells May Play a Critical Role in Modulating Immune Homeostasis in Silicosis Patients

Abstract: Silicosis is characterized by chronic lung inflammation and fibrosis, which are extremely harmful to human health. The pathogenesis of silicosis involves uncontrolled immune processes. Evidence supports that regulatory B cells (Bregs) produce negative regulatory cytokines, such as IL-10, which can negatively regulate immune responses in inflammation and autoimmune diseases. Our previous study found that IL-10-producing B cells were involved in the development of silica-induced lung inflammation and fibrosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 52 publications
(56 reference statements)
4
38
1
1
Order By: Relevance
“…Besides their established phenotype in mice, the molecules CD5 and CD1d might also define a human Breg population (15,33,34). It is important to separate these cells from CD5expressing B1a B cells.…”
Section: Figure 3 |mentioning
confidence: 99%
“…Besides their established phenotype in mice, the molecules CD5 and CD1d might also define a human Breg population (15,33,34). It is important to separate these cells from CD5expressing B1a B cells.…”
Section: Figure 3 |mentioning
confidence: 99%
“…However, it is becoming evident that most available anti-inflammatory drugs ( 34 , 35 ) or cytokine inhibitor therapy ( 36 ) are not effective for particle-exposed patients. Human validation studies have also failed to confirm the use of inflammatory mediators as biomarkers for univocally detecting the health effects of particles ( 37 ).…”
Section: Recent Clinical and Experimental Findings That Challenge Thementioning
confidence: 99%
“…However, several lines of evidence have demonstrated that IL-10 (as TGF-β) possesses deleterious and pro-fibrotic functions after particle exposure. First, lung expression of IL-10 was intimately associated to the development of particle-induced fibrosis and cancer and could explain the absence of chronic and progressive inflammation in human and mouse models ( 37 , 53 , 57 , 84 88 ). Additional data supports that IL-10 participates in the extension of fibrosis since targeted overexpression of IL-10 in the murine airways caused, by itself, collagen deposition, accumulation of mesenchymal cells and airway remodeling with fibrosis ( 89 , 90 ).…”
Section: Involvement Of the Anti-inflammatory And Immunosuppressive Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation and recruitment of macrophages and neutrophils into the lung parenchyma, particularly on the NALP-3 inflammasome, drives the production of inflammatory cytokines and chemokines, thus promoting and intensifying local tissue damage that culminates in collagen and elastin deposition and lung remodeling. [11][12][13][14][15] Among those mediators implicated in the pathogenesis of silicosis, the interleukins IL-1β, IL-4, IL-5, IL-6, IL-8, and IL-10 12, [16][17][18] ; tumor necrosis factor (TNF) and its receptor sTNFR1 and sTNFR2; transforming growth factor β (TGF-β), and the chemokines CCL3 and CCL24 have been highlighted. 19,20 Other inflammatory markers such as bone morphogenetic protein (BMP2) and chemokines CCL5 and CXCL16 have been shown to mediate vascular plasticity, angiogenesis, and leukocyte recruitment in distinct tissues 21,22 and, more recently, implicated in potentiating respiratory-inflammatory processes driven by T-cells and macrophages in asthma 23,24 and viral infections.…”
Section: Introductionmentioning
confidence: 99%